Earnings, Rents, and Competition in the Airline Labor Market - Hirsch, Barry T.; Macpherson, David A. (Journal of Labor Economics, 2000)
This article offers an explanation of the postinjury employment, wage, and accommodation patterns of permanently impaired workers. In particular, it argues that the observed tendency of time‐ofaccident employers to rehire at the preinjury wage, accommodate, and then, perhaps, quickly terminate the impaired worker, is a manifestation of the worker's preferred contract. That contract is characterized by wage inflexibility. By removing the opportunity for the postinjury employer to underreport productivity, this contract creates an incentive for the worker to attempt to functionally adapt to the impairment, thereby increasing expected lifetime utility.